Turnover intention mahasiswa generasi Z: Pengaruh work-life balance dan kompensasi dengan mediasi kepuasan kerja - Maidir Sutino; Syahbandi Syahbandi; Ikram Yakin; Titik Rosnani; Hasanudin Hasanudin (Nur Science Institute, 2026)
This study aims to analyze the influence of work-life balance and compensation on turnover intention, both directly and through job satisfaction as a mediating variable, among Generation Z employees working in coffee shops in Pontianak City. The method used is quantitative, employing Partial Least Squares Structural Equation Modeling (PLS-SEM). The research sample involved 194 respondents, namely students aged 18–26 years who are still actively studying and have at least one year of work experience in a coffee shop, which was selected through the purposive sampling method. The results of the study show that Work-Life Balance has a negative and significant effect on Turnover Intention, both directly and indirectly through Job Satisfaction, as a mediating variable, among Generation Z employees working in coffee shops in the Pontianak City area. Meanwhile, compensation does not have a significant direct effect on Turnover Intention, but it has a positive and significant effect on Job Satisfaction, which, in turn, reduces Turnover Intention. In addition, Job Satisfaction has been shown to have a negative and significant effect on Turnover Intention and to mediate the relationship between Work-Life Balance and Compensation for Turnover Intention.